DEVELOPMENT OF LOCAL CULTURE-BASED STEAM LEARNING EVALUATION TOOL IN LABUAN, PANDEGLANG-BANTEN - Ramdhani, Sendi; Rokhiyah, Isti; Sapriati, Amalia; Rosita, Tita; Ambar Puspitasari, Kristanti (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Community Service Activities (PkM) carried out in Labuan Regency aim to improve the ability of elementary schools to develop STEAM learning evaluation tools based on local culture. The main target audience of this training activity is elementary school teachers in the Labuan Banten sub-district. Based on the identification of the problem, it is known that elementary school teachers in Labuhan lack training in the development of evaluation tools, especially in STEAM learning. As a teacher, the ability to develop evaluation tools is needed to see student development. The target to be achieved in the implementation of this PKM is to increase the knowledge and skills of elementary school teachers in developing STEAM learning evaluation tools based on local culture. The method of implementing this community service activity is to use a training method that is packaged into two activities, namely seminars and workshops. The training activity began with a one-day seminar with an offline method to provide material on the scope of local culture-based STEAM learning evaluation tools, furthermore, the teachers trained themselves to develop evaluation tools with assistance from the PKM Team through online methods. The output of this service activity is a local culture-based STEAM learning evaluation tool developed by teachers and scientific publications. The results of this PkM are 3 packages of evaluation tools.